Training on Making Liquid Laundry Soap as an Effort to Realize a Home Industry MSME Unit for Women Residents of Talang Sungai Limau Village, Rakit Kulim District, Indragiri Hulu Regency, Riau Province - Arhipen Yapentra; Putra Budi Ansori; Risman Risman; Muh. Ali Aqsa; Yulia Harwina; Diana Sri Dewi; Mahbubah Srimulatsih (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This article was created as one of the outcomes of Community Service activities in STIE Riau's assisted villages as partners, namely Talang Sungai Limau Village, Rakit Kulim District, Indragiri Hulu Regency, Riau Province. Held on September 24-25 after a series of preparatory activities. This activity aims to increase the skills and interest of PKK women in partner villages to make household production as well as efforts to foster interest in MSMEs for residents as an effort to improve the family economy. Activities carried out in lectures, discussions and practice of making liquid laundry soap to packaging and explaining simple marketing methods. On the first day, an introduction to materials and methods of making as well as the practice of making liquid laundry soap is given. After settling for 24 hours, packaging and an explanation of sales are carried out as well as an estimate of the capital and profits obtained from one package of liquid laundry soap which produces 100 bottles with a volume of 200 ml.